Analisis Pengembangan Posyandu Harapan Pertiwi Untuk Meningkatkan Kesehatan Bayi Dan Balita - Endang Khoirunnisa; Hari Wujoso; Nunuk Suryani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: The analysis of development of integrated service post to improve the health of Earth HopekInfant andkToddlerkCasekStudykonkthekHamletkthekVillagekDruwo, Bangunharjo,Sewon BantulkYogyakarta. ThesisThekpostgraduatekProgramkthehUniversitykofkSebelaskMaretkSurakarta.Objective: To know determine the planning, the organization, the implementation, the monitoring and the evaluation, the results achieved, obstacles in the face in the Integrated Service Post Pertiwi Hope of the Hamlet the Village Druwo Bangunharjo SewonkBantulkYogyakarta.Method: The methode used in this study is the qualitative with the case study design is descriptive. Integrated Service Post the Analysis Unit is in the hamlet of Hope Pertiwi Druwo Bangunharjo Sewon Bantul Yogyakarta. Purposively sampling data taken the through in-depth interviews with the observation with checklist. The Analysis of data by the building the technical explanation explanation and analysis of the results of interviews and observations penulusuran checklist document.Results: Research shows that planning activities in the hamlet of Integrated Service Post Pertiwi Hope the hamlet the village Druwo Bangunharjo Sewon Bantul Yogyakarta is in good order to follow the rules of planning, involving all the components and produce planning documents, organizationalkstructurekofkthekimplementingkIntegratedkServicekPostkiskankinformalkorganizationkinkthelcommunity.Conclusion: of this study are as follow: the analysis of the implementation of Integrated Service Post of Pertiwi Hope of the hamlet the village Druwo Bangunharjo Sewon Bantul Yogyakarta.Keywords: The analysis, Integrated Service Post